Identification of selenomethionine, selenocysteine, and Se-methylselenocysteine in the selenium-enriched common ice plant - Tobe, Ryuta; Koga, Hiroki; Tani, Yasushi; Tajima, Hirotaka; Tsuji, Akihisa; Mihara, Hisaaki (Biomedical Research on Trace Elements, 2017)
The essential trace element selenium (Se) plays a fundamental role in human health. Plant foods, such as vegetables, serve as the most common dietary sources of Se. Recently, novel seleno-amino acids, including Se-methylselenocysteine, γ-glutamyl-Se-methylselenocysteine, and selenocystathionine, have been found in certain plants and their benefits for human health are increasingly being recognized. The common ice plant, Mesembryanthemum crystallinum L., is an edible halophyte that accumulates D-pinitol, which exerts an insulin-like effect. However, little is known about the metabolism of seleno-amino acids in the common ice plants. Here we show that the common ice plant exhibits relatively high tolerance to both selenite and selenate and accumulated Se upon treatment with inorganic Se compounds. Speciation analysis revealed that selenocystine, selenomethionine, and Se-methylselenocysteine were present in the leaf of the Se-treated common ice plant. Interestingly, a significant portion of these Se-amino acids was liberated by a protease treatment, suggesting that the common ice plant can metabolize the inorganic Se compounds to the seleno-amino acids that were eventually incorporated nonspecifically into proteins. This study shows that the Se-enriched common ice plant can be a healthy source of Se in the human diet.